2016
DOI: 10.1007/978-981-287-688-1_3
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Conversion of Short-Chain Carbohydrates: A Mechanistic Insight

Abstract: This chapter discusses recent insights in the conversion of short carbohydrates, viz., sugars containing four or less carbon atoms. Rather than summarizing product yields from such sugars and reported catalysts for the conversions, the focus lies on understanding the underlying mechanisms. These short carbohydrates can lead to a broad spectrum of products, ranging from platform chemicals such as lactic acid and ethylene glycol to high-value chemicals such as α-hydroxy-γ-butyrolactone and even fuels. Different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 121 publications
0
4
0
Order By: Relevance
“…The EoL PLA ( 1 ) is degraded with the degradation reagent methanol and with the support of a catalyst to form as main chemical methyl lactate ( 2 ). Subsequently, methyl lactate ( 2 ) can be transformed to compound 3 (lactide), which is a fundamental compound in the industrial production chain of PLA (Scheme ) . As second product methanol is produced, which can be recycled for further degradation; therefore, reduced amounts of waste are generated and the whole process is made highly atom efficient.…”
Section: Methodsmentioning
confidence: 99%
“…The EoL PLA ( 1 ) is degraded with the degradation reagent methanol and with the support of a catalyst to form as main chemical methyl lactate ( 2 ). Subsequently, methyl lactate ( 2 ) can be transformed to compound 3 (lactide), which is a fundamental compound in the industrial production chain of PLA (Scheme ) . As second product methanol is produced, which can be recycled for further degradation; therefore, reduced amounts of waste are generated and the whole process is made highly atom efficient.…”
Section: Methodsmentioning
confidence: 99%
“…In the literature, it is reported that PVA is produced by GLA dehydration. 27 Some authors hypothesized the possibility to produce PVA directly by dehydrating DHA, which is unlikely based on common reactivity trends in organic chemistry. 27 However, none of these possibilities explain an apparent second-order reaction.…”
Section: Nbpo Lapomentioning
confidence: 99%
“…27 Some authors hypothesized the possibility to produce PVA directly by dehydrating DHA, which is unlikely based on common reactivity trends in organic chemistry. 27 However, none of these possibilities explain an apparent second-order reaction. DHA and GLA are in equilibrium with each other, although DHA seems to be always the most abundant species in solution.…”
Section: Nbpo Lapomentioning
confidence: 99%
See 1 more Smart Citation